Nationwide retrospective observational study of idiopathic dendriform pulmonary ossification: clinical features with a progressive phenotype. Issue 1 (26th September 2022) - Nishioka, Yasuhiko; Toyoda, Yuko; Egashira, Ryoko; Johkoh, Takeshi; Terasaki, Yasuhiro; Hebisawa, Akira; Abe, Kinya; Baba, Tomohisa; Fujikura, Yuji; Fujita, Etsuo; Hamada, Naoki; Handa, Tomohiro; et al.
Abstract : Background: Diffuse pulmonary ossification is a specific lung condition that is accompanied by underlying diseases. However, idiopathic dendriform pulmonary ossification (IDPO) is extremely rare, and the clinical features remain unclear. In this study, we aimed to report the clinical characteristics of IDPO. Methods: We conducted a nationwide survey of patients with IDPO from 2017 to 2019 in Japan and evaluated the clinical, radiological, and histopathological findings of patients diagnosed with IDPO. Results: Twenty-two cases of IDPO were identified. Most subjects (82%) were male, aged 22–56 years (mean (SD), 37.9 (9.1)) at diagnosis. Nearly 80% of the subjects were asymptomatic, and the condition was discovered during a medical check-up. However, 36% of the subjects showed a decline in forced vital capacity (%FVC) predicted <80% at diagnosis. The typical radiological features of high-resolution CT (HRCT) are calcified branching structures that are predominantly distributed in the lower lung fields without any other conspicuous finding. Histopathological analysis also showed dendriform ossified lesions from the intraluminal areas to interstitial areas. Notably, during the follow-up period of 20 years, disease progression was found in 88% on HRCT and more than 50% on pulmonary function tests (FVC and/or forced expiratory volume in 1 s). Two cases with rapid decline of 10% /year in %FVC predicted were observed. )) at diagnosis. Nearly 80% of the subjects were asymptomatic, and the condition was discovered during a medical check-up. However, 36% of the subjects showed a decline in forced vital capacity (%FVC) predicted <80% at diagnosis. The typical radiological features of high-resolution CT (HRCT) are calcified branching structures that are predominantly distributed in the lower lung fields without any other conspicuous finding. Histopathological analysis also showed dendriform ossified lesions from the intraluminal areas to interstitial areas. Notably, during the follow-up period of 20 years, disease progression was found in 88% on HRCT and more than 50% on pulmonary function tests (FVC and/or forced expiratory volume in 1 s). Two cases with rapid decline of 10% /year in %FVC predicted were observed. Conclusions: IDPO develops at a young age with gradually progressive phenotype. Further research and long-term (>20 years) follow-up are required to clarify the pathogenesis and clinical findings in IDPO.